Achieving the Sustainable Development Goals through Financial Inclusion: A Bibliometric and Content Analysis - Monika Chandel; Manpreet Arora (Tourism & Management Studies)
This article presents a bibliometric study that explores the connections between the literature on achieving Sustainable Development Goals (SDGs) through financial inclusion using a relational approach. The findings highlight key publication trends, the most prolific countries, leading contributors, highly cited articles, and the most impactful journals in this field. Additionally, content analysis reveals four emerging areas of research: “financial technology and SDGs,” “social capital,” “microfinance and women empowerment,” and “green finance.” Based on these insights, the study recommends that managers prioritise adopting digital technologies to foster financial inclusion, build robust networks to enhance resilience, empower women through tailored financial products, and integrate the Sustainable Agenda 2030 into financial strategies. Organisations can promote inclusion, resilience, and sustainable growth by aligning with these evolving research domains while advancing the SDGs. The results aim to inspire and guide management and economic researchers toward achieving the SDGs and serve as a foundation for realising Agenda 2030 objectives.